2017
DOI: 10.1111/jfs.12397
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patulin adsorption efficacy from aqueous solution by water‐insoluble corn flour

Abstract: This study investigated water-insoluble corn flour (WICF) as a novel biosorbent for removing patulin from aqueous solutions, including contaminated fruit juices. Batch adsorption experiments were performed to assess the effect of granularity of WICF, adsorbent dosage, contact time, temperature, pH, and initial patulin concentration. The results showed that the maximum removal percentage of 92.21% was achieved at 37 8C, pH value of 4.0 in 100 mg/L patulin concentration for 25 hr. The adsorption data could be we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
(76 reference statements)
1
9
0
Order By: Relevance
“…Clearly, TETA‐WICF/MCR showed the best adsorption capacity of patulin, and this might be because more amino (–NH 2 ) groups can be covalently bonded by modification with TETA, as well as the existence of hydroxyl (–OH) groups in adsorbent, resulting in more adsorption sites for the excellent removal efficiency of patulin by TETA‐WICF/MCR. We also found that the patulin removal percentage considerably increased with an increase of adsorbent dosage, probably due to the accessibility of high affinity binding sites as the increase of the mass (Guo et al., 2018).…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…Clearly, TETA‐WICF/MCR showed the best adsorption capacity of patulin, and this might be because more amino (–NH 2 ) groups can be covalently bonded by modification with TETA, as well as the existence of hydroxyl (–OH) groups in adsorbent, resulting in more adsorption sites for the excellent removal efficiency of patulin by TETA‐WICF/MCR. We also found that the patulin removal percentage considerably increased with an increase of adsorbent dosage, probably due to the accessibility of high affinity binding sites as the increase of the mass (Guo et al., 2018).…”
Section: Resultsmentioning
confidence: 84%
“…As apparent from FTIR spectroscopy spectrums, the characteristic peak of the pyranose ring around 896 cm −1 remained unchanged (Figures 2C–2E), implying that the structure of chitosan was not destroyed during the whole preparation process (Liao et al., 2016); and additional peaks located at 929 cm −1 (skeletal mode vibrations of a‐1,4 glycosidic linkage [C–O–C]), 761 cm −1 (C– stretching), and 706 cm −1 (skeletal modes, C–C stretching) occurred as a result of the immobilization of WICF (Guo et al., 2018); it was also found that another characteristic peak of 580 cm −1 , which corresponded to the Fe–O bond appeared in the spectrum of TETA‐WICF/MCR, indicating that the Fe 3 O 4 nanoparticles were successfully assembled on chitosan (Wang et al., 2017). In the specimen of C‐WICF/MCR (Figure 2C), the intensity of the peak at 1594 cm −1 weakened obviously, revealing that the amino groups decreased and the reaction between glutaraldehyde and amino groups was dominant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations